2014
DOI: 10.1038/hr.2014.109
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal pressure-wave reflection in pregnant women with chronic hypertension: association with maternal and fetal outcomes

Abstract: The current study tested the hypothesis that abnormal pressure-wave reflection may have an important role in identifying pregnant women with chronic hypertension who might develop pre-eclampsia (PE) and/or fetal growth restriction. Pulse-wave analyses were performed to assess maternal arterial stiffness during 26-32 weeks of gestation in 41 women with chronic hypertension. We measured the central systolic pressure (CSP) and augmentation index (AIx) noninvasively using pulse waveforms of the radial artery with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
0
11
0
1
Order By: Relevance
“…Limits of y-axis represent maximum and minimum values within dataset. cross-sectional cohort study of 41 pregnant women with chronic hypertension, conducted by Tomimatsu et al 12 , also demonstrated an association between increased AIx-75 and SPE. This study found that increased brachial 12-15.9 SPE readings (n) CHT control readings (n) of subdividing their cohort reduced the power and may have affected the results.…”
Section: Figurementioning
confidence: 84%
See 3 more Smart Citations
“…Limits of y-axis represent maximum and minimum values within dataset. cross-sectional cohort study of 41 pregnant women with chronic hypertension, conducted by Tomimatsu et al 12 , also demonstrated an association between increased AIx-75 and SPE. This study found that increased brachial 12-15.9 SPE readings (n) CHT control readings (n) of subdividing their cohort reduced the power and may have affected the results.…”
Section: Figurementioning
confidence: 84%
“…In those who developed SPE, compared with those who did not, the central aortic pressure was increased, but there was no significant difference in PWV or AIx‐75. A cross‐sectional cohort study of 41 pregnant women with chronic hypertension, conducted by Tomimatsu et al , also demonstrated an association between increased AIx‐75 and SPE. This study found that increased brachial SBP and central aortic pressure predated the development of SPE with SGA at 26 to 32 weeks' gestation compared to women with chronic hypertension who had SPE alone, SGA alone or no SPE or SGA.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Importantly, there is an important interaction bewteen arterial stiffness and hypertension. In this regard, arterial stiffness has been associated with brachial blood pressure in pregnant women [6]. There are increases in forearm vascular resistance in young men with first-degree relatives suffering from essential hypertension [7].…”
Section: Arterial Stiffness and Hypertensionmentioning
confidence: 99%